Analysing genome sequences and associated metadata during the COVID-19 pandemic in Iraq revealed points to be improved: An observational retrospective study - Ali Hadi Abbas; Aoula Al-Zebeeby; Mohammed Al-Saadi; Ahmed Jasim Neamah (PLoS ONE, 2025)
The COVID-19 pandemic started in Wuhan China and rapidly transmitted worldwide, the illness is characterised by respiratory manifestations like coughing, breathing difficulties and pneumonia that could lead to death. Real-time whole genome sequencing of severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) was adopted in many countries to track the infection dynamics and evolution of the virus. In parallel with the global efforts, genome sequencing trials were established in Iraq during the COVID-19 pandemic, however, this new approach has not been assessed yet. Therefore, for better readiness and improvement for future pandemics, here we obtained all genomes of SARS-CoV-2 virus from Iraq (182) that were deposited in National Center for Biotechnology Information (NCBI) during the period (2020–2023). Statistical analyses of sample size, distribution and other epidemiological parameters from associated metadata, as well as the quality of genome sequences were assessed. Our data analyses highlighted some drawbacks that could be improved, namely, that most genomic sequences (62%) were collected from only two cities, a low sample size was noticed and sequencing quality was inconsistent. There was a shortage and impairment of sequencing facilities especially those of the Ministry of Health. Consequently, genome sequencing should be achieved in centres that produce the best quality. The results revealed the importance of well-documented and high-quality sequences that represent many important cities in the country, which is crucial to draw a clear projection for health officials on infection dynamics and tracking viral evolution to help in taking successful steps towards infection control.